2017
DOI: 10.1016/s0168-8278(17)31457-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of glecaprevir/pibrentasvir in Japanese patients with chronic genotype 2 hepatitis C virus infection with and without cirrhosis

Abstract: Background The once-daily, all oral, RBV-free, pangenotypic direct-acting anti-viral regimen consisting of co-formulated NS3/4A protease inhibitor glecaprevir and NS5A inhibitor pibrentasvir (G/P), demonstrated high rates of sustained virologic response (SVR) in phase 2 and 3 studies outside Japan. Methods CERTAIN-1 is a phase 3, open-label, multicenter study assessing the safety and efficacy of G/P (300/ 120 mg) once daily in Japanese patients with chronic HCV GT1 infection. Patients without cirrhosis receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…Additionally, there were no cases of hepatic decompensation, and no events consistent with drug-induced liver injury were reported. The low rates of laboratory abnormalities observed in this study were also observed in Japanese patients with GT 1 or 2 infection without cirrhosis and with compensated cirrhosis enrolled in the CERTAIN studies and treated with G/P (reported elsewhere [ 17 , 18 ]). Similar overall safety results were observed across all phase 2 and phase 3 studies conducted outside Japan.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, there were no cases of hepatic decompensation, and no events consistent with drug-induced liver injury were reported. The low rates of laboratory abnormalities observed in this study were also observed in Japanese patients with GT 1 or 2 infection without cirrhosis and with compensated cirrhosis enrolled in the CERTAIN studies and treated with G/P (reported elsewhere [ 17 , 18 ]). Similar overall safety results were observed across all phase 2 and phase 3 studies conducted outside Japan.…”
Section: Discussionsupporting
confidence: 80%
“…CERTAIN-1 is a phase 3, open-label, multicenter study assessing the safety and efficacy of G/P (300/120 mg) once daily in Japanese patients with HCV infection. Results from substudy 1 where HCV GT1-infected patients without cirrhosis were treated for 8 weeks with G/P or 12 weeks with ombitasvir/paritaprevir/ritonavir, as well as patients in substudy 2 with HCV GT1 and GT2 infection and compensated cirrhosis treated with G/P for 12 weeks have been reported elsewhere [ 17 , 18 ]. Here we report on the remainder of patients in substudy 2 who belong to four special populations: HCV GT1- or GT2-infected patients who failed prior DAA-treatment including patients with compensated cirrhosis, GT1 or GT2 HCV-infected patients with severe renal impairment and compensated cirrhosis, GT3 HCV-infected patients who were treatment-naive or IFN treatment-experienced, all of whom received treatment with G/P for 12 weeks, and patients with GT1 or GT2 HCV infection with severe renal impairment without cirrhosis who received treatment for 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Seventeen studies fulfilled the eligibility criteria and were included in the analysis. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The reasons for excluding the remaining studies are detailed in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Four studies compared the SVR12 rates in patients with prior DAA-failure, 20,27,32,36 nine studies reported efficacy in the presence of baseline RAS in patients withGT1 20,21,27,29,[31][32][33][34]36 and five studies reported the efficacy and baseline RAS in patients with GT3. 29,31,33,34,36 Six studies excluded cirrhotic patients, [25][26][27]29,31,33 three studies included patients with concomitant chronic kidney disease and HCV infection, 20,28,33 one study evaluated patients with HIV-HCV co-infection.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation